Shōjo Character in Miyazaki’s Kiki’s Delivery Service as Challenging the Archetype: A Semiotic Study - Wedhowerti (JOALL (Journal of Applied Linguistics and Literature), 2024)
Studio Ghibli has made great animated films for more than three decades. One of its great animators is Hayao Miyazaki. Being famous for his award-winning and picturesque films, Miyazaki has proven to be a highly skilled animator presenting a catchy shōjo with distinctive characters. His shōjo named Kiki in Kiki’s Delivery Service has peculiar traits. This research aims at proving the opposition of Kiki to the common Japanese female character archetype. Eight pieces of data are in the form of screen captures to be studied semiotically. As part of social science research, this study is qualitative in nature. By employing Barthesian semiotic theory and Sugawa-Shimada’s theory of shōjo, it is evident that Kiki opposes the archetype of Japanese female characters. Kiki is portrayed as independent, assertive, not depending on one specific type of magical weapon, wearing a simple black witch dress, able to make prompt and clear decisions, doing daily chores, and having magical power that might be gone anytime due to some psychological reasons. Theoretically, this study contributes to the development of the linguistic field, particularly the stream of semiotics. This research also benefits researchers, film-makers, film audiences, and Studio Ghibli’s enthusiasts in a semiotic way that Kiki as shōjo is constructed with great empowerment opposing the common stereotype of a female character.